Optimizing the frequency of ultrasonic tomography system with a metal pipeline - Abbaszadeh, J. (International Frequency Sensor Association (IFSA), 2012)
Ultrasonic Tomography has an important role in industry to produce scanned images for various propose. In this paper, producing the cross sectional images of pipe for detecting percentage of attendance of solid, liquid and gas inside the metal pipe has been investigated. The correct method of mounting of Ultrasonic sensors and behavior of the ultrasonic wave propagation in different layers has been simulated by the use of finite element software (COMSOL Multiphysics 3.5). To increase in practical nondestructive evaluation and inspection, we should increase our understanding of the basic physics and wave mechanics associated with guided wave inspection. Finding the proper ultrasonic sensor base on its efficiency is the main step of designing an Ultrasonic Tomography system. This is done by estimating the resonance frequency of sensor due to manner of ultrasonic wave propagation in different frequencies shown in simulation results. Optimum frequency of the system is proposed 45 kHz.